ANALISIS TREN NILAI TUKAR PETANI TANAMAN PANGAN PROVINSI KEPULAUAN BANGKA BELITUNG - Apriyono, Apriyono (Universitas Islam Balitar, 2021)
The sustainability of rice or food crop farming depends on the level of welfare of the farmers. One approach to measuring the purchasing power of farmers in rural areas is the Farmer Exchange Rate (NTP). The purpose of this study was to determine the development of the achievement level of the Exchange Rate of food crop farmers in Bangka Belitung from 2013-2020 with the method of analysis using quantitative descriptive methods. The results showed that the average farmer exchange rate from 2013-2020 was 93.98 percent, still below the index value of 100, which means that food crop farmers in Kepulauan Bangka Belitung Province are still not prosperous.